2018
DOI: 10.1002/pc.24973
|View full text |Cite
|
Sign up to set email alerts
|

Glass/Epoxy and Hemp/Bio based epoxy composites: Manufacturing and structural performances

Abstract: Biocomposite materials are nowadays often considered as a valid substitution of fiberglass reinforced (FGR) polymers in many relevant applications, especially thanks to the lower costs and environmental impact of the natural fibers. Conversely, they remain mainly confined to nonstructural applications. In consideration of the similar specific properties of glass and hemp fibers, the aim of this work is to compare a biocomposite component, for structural application, with a FGR-epoxy one. The comparison is focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…In general, natural fibers with higher strength and Young' s modulus have a higher cellulose content, a longer cell length, and a lower microfibrillar angle, such as in the case of hemp fiber [14,20,21]. The degradation of natural fibers depends on individual chemical composition; lignin is mainly responsible for UV and fire degradation, whereas hemicelluloses are responsible for biological degradation, thermal degradation, and high moisture absorption [11,14,22]. Table 2 shows the physical and mechanical properties of natural fibers and the main type of glass fiber (E-glass).…”
Section: Natural Fibers: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, natural fibers with higher strength and Young' s modulus have a higher cellulose content, a longer cell length, and a lower microfibrillar angle, such as in the case of hemp fiber [14,20,21]. The degradation of natural fibers depends on individual chemical composition; lignin is mainly responsible for UV and fire degradation, whereas hemicelluloses are responsible for biological degradation, thermal degradation, and high moisture absorption [11,14,22]. Table 2 shows the physical and mechanical properties of natural fibers and the main type of glass fiber (E-glass).…”
Section: Natural Fibers: General Considerationsmentioning
confidence: 99%
“…Data from: [8,11,18,20,23]. The mechanical properties of natural fibers depend on their physical, chemical, and morphological properties as well as growing conditions, harvesting time, extraction method, treatment, and storage procedures [3,7,17,18,22,23]. Pickering et al [24] reported that the strength of hemp fibers was reduced by 15% over five days after optimum harvest time, which was found to be 114 days, with an average tensile strength of 857 MPa and a Young's modulus of 58 GPa.…”
Section: Natural Fibers: General Considerationsmentioning
confidence: 99%
“…This fiber could be prepared from the fruit of the plant. Its density measures 0.84 g/cm 3 and tensile strength could be higher than other natural fibers like jute, Spinifex littoreus, and areca. Krishnan et al [12] conducted a research on automobile break pad using C. urens and SiC fillers.…”
Section: Introductionmentioning
confidence: 95%
“…There is lot of research going on in developing of biodegradable materials and agricultural biomass to reduce the severity of environmental concerns. [ 3 ] There is more number of new sustainable fibers and particles are developed from plant and animal biomasses by researchers all over the world to prepare ecofriendly composite materials, which are less harm to environment. The fiber or particle acts as strength boosting elements in composites, moreover the particle addition could develops some special properties too.…”
Section: Introductionmentioning
confidence: 99%
“…However, the advantages of nanocomposites depend on the dispersion of nanoparticles in the polymer matrix . Today's, the biodegradable polymers are attracting much interest, due to the increasing consumption of plastics and the limited amount of raw materials . Poly(lactic acid) (PLA) and poly(ethylene oxide) (PEO) are biodegradable and biocompatible polymers displaying good characteristics for biomedical applications .…”
Section: Introductionmentioning
confidence: 99%